(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2022)
Background: Obesity associated with diabetes is a life-threatening condition. Currently, surgery represents an effective and long-lasting therapeutic option to treat it, with gastric bypass being the standard procedure, demonstrating a significant effect on weight loss and resolution of diabetes. Objective: To compare results that demonstrate the efficacy of each gastric bypass technique in the ¨Abel Gílbert Pontón¨ hospital, focusing on the benefits, complications, and evolution of each group. Methodology: Observational study, retrospective, analytical, comparative, and longitudinal, carried out at the Abel Gílbert Pontón Hospital, during the period 2015-2019. The population consisted of patients diagnosed with obesity and type 2 diabetes mellitus who underwent gastric bypass. Results: 76 patients were analyzed, of which 46 underwent BAGUA and 30 under RYGB. When comparing weight loss, no significant difference was noted in any of the follow-up times (3, 6, and 12 months), but significant differences were observed regarding surgical time, hospital stay, and ICU admission, in favor of BAGUA. Greater remission of diabetes mellitus was evidenced for BAGUA. RYGB was more related to complications (bleeding, anastomotic leak and reoperation). There was no difference in the presence of gastroesophageal bile reflux. One patient died (1.32%), who had undergone RYGB. Conclusions: BAGUA is an effective procedure for weight loss, with equal or better benefits than RYGB, and has greater effectiveness in remission of diabetes mellitus; Furthermore, it is safer, with less morbidity and less reoperation.